2013
DOI: 10.1016/j.arabjc.2010.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new (pyrazol-1-yl)(7-nitro-1h-indol-2-yl)ketone derivatives

Abstract: International audienceThe condensation of 7-nitroindole-2-carbohydrazide derivatives with acetylacetone lead to (pyrazol-1-yl)(7-nitroindol-2-yl)ketones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Phenylhydrazones represent the principal starting material in the synthesis of indole derivatives. Some works have reported the synthesis of indole derivatives from the mixture of the two tautomers of phenylhydrazone without separation (Parmerter et al, 1958;Murakami et al, 1999;Narayana et al, 2005;El Kihel et al, 2013). Among these, Murakami et al (1999) reported the separation of the mixture of indole normal and indole abnormal.…”
Section: Structure Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenylhydrazones represent the principal starting material in the synthesis of indole derivatives. Some works have reported the synthesis of indole derivatives from the mixture of the two tautomers of phenylhydrazone without separation (Parmerter et al, 1958;Murakami et al, 1999;Narayana et al, 2005;El Kihel et al, 2013). Among these, Murakami et al (1999) reported the separation of the mixture of indole normal and indole abnormal.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…However, the synthesis of phenylhydrazone by the condensation of phenylhydrazine with carbonyl compounds or by condensation of o-nitroaniline diazonium with ethyl -methylacetoacetate in basic medium (Japp-Klingemann reaction) lead to two tautomeric products (Murakami et al, 1993;Wagaw et al, 1999;Lipinska et al, 1999). Based on our indole synthesis program (El Kihel et al, 2013, 2007El Ouar et al, 1995), we report in this work the isolation of the majority product of the mixture of the two tautomers.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…For biochemical properties of indoles, see: Kuethe et al (2005); Smith et al (1998). For medicinal activity, see: El Kihel et al (2007Kihel et al ( , 2013; Penning et al (1997); Dumas et al (2000). For starting materials, see: El Ouar et al (1995 Symmetry codes: (i) Àx þ 1; Ày; Àz þ 2; (ii) x; y þ 1; z þ 1; (iii) Àx þ 1; Ày; Àz þ 1.…”
Section: Related Literaturementioning
confidence: 99%
“…In previous papers (El Kihel et al, 2007;2013;El Ouar et al, 1995), we have reported some reactions of 7-aminoindoles and the condensation of the 7-nitroindole-2-carbohydrazide with acetylacetone. Herein, we report the Table 2.…”
Section: Related Literaturementioning
confidence: 99%